Quantification of purified endogenous miRNAs with high sensitivity and specificity - Soochul Shin; Yoonseok Jung; Heesoo Uhm; Minseok Song; Soomin Son; Jiyoung Goo; Cherlhyun Jeong; Ji-Joon Song; V. Narry Kim; Sungchul Hohng (Nature Communications, 2020)
MicroRNAs are potentially powerful biomarkers, though clinical use requires rapid and reliable profiling. Here the authors report amplification-free multicolour single-molecule imaging with single base mismatch sensitivity.